(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Leukemia is one type of blood cancer developed in the bone marrow and other blood-forming organs. Based on a combination of onset speed and cell origin, leukemia can generally be divided into four subtypes: acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML‚ (chronic lymphocytic leukemia (CLL), and chronic myelogenous leukemia (CML). Methods: A total of 3102 eligible leukemia cases were documented in the Iraqi Center for Hematology in the City of Medicine in Baghdad between January 2018 and December 2019. 1402 documented in 2018 and 1700 in 2019 for all types of cancer, Patients ages were between 1 year and 90 years, among all leukemia cases, the mostly 36% (n = 730) were aged ?15 years. Results In our study males accounted for a higher proportion of leukemia patients, 58 % compared to 42% females, ALL was the more prevalent type among the studied group for both years ; contribute% 55.17 din male %53.45 in female, followed by AML 36.87% vs 40.27% , CLL 5.23% vs 2.22% and CML 2.73% vs 4.06% in male and female respectively. Conclusion It was observed that the prevalence of leukemia in Baghdad increased between (2018 -2019) from 1402 to 1700, the youngest age 15 registered most of leukemia cases. . Males were mostly victim of the disease as compared to females which were less frequent. It was observed that acute lymphoblastic leukemia (ALL) was most common type of leukemia.